Monarch butterflies (Danaus plexippus) only use magnetic cues for migratory directionality with orientation re-calibrated by coldness - Samuel A. Shively-Moore; Stephen F. Matter; Patrick A. Guerra (PLoS ONE, 2025)
Each fall, Eastern North American monarch butterflies (Danaus plexippus) leave their northern range and migrate to their overwintering sites high atop mountains in central Mexico. Although monarchs primarily rely on the use of a bidirectional time-compensated sun compass to maintain southwards directionality en route to Mexico, on overcast sky days when directional daylight cues are unavailable, monarchs can use an inclination-based magnetic compass to maintain correct directionality. As compass cues can only be used to determine direction, monarchs must use other mechanisms for recognizing, locating, and ultimately stopping at their overwintering sites. Although previous work found no evidence of monarchs using a fine-scale magnetic map for locating their specific overwintering sites, monarchs might still use magnetic cues in a general sense, such as when recognizing that they have overshot their destination or have gone off course. Here, using righting response orientation trials, we show that fall monarchs maintain equatorward (southward) orientation even when tested under artificially generated magnetic field conditions consistent with either their overwintering sites or magnetic conditions geographically south of these sites. We also found that fall migrants exposed to overwintering-like coldness reverse their orientation poleward (northward). This result indicates that the monarch’s magnetic compass is also recalibrated by the cold temperature microenvironment at the overwintering sites, as has been shown previously with its time-compensated sun compass. Our results indicate that migratory monarchs must use other cues for locating and stopping at their migratory destination. Our discovery that coldness recalibrates multiple compass mechanisms in a long-distance migratory species underscores the threat of climate change and corresponding increasing temperatures on animal migration.